Rapamycin affects the proliferation of triple-negative breast cancer cells by regulating TRAP1 - Huang Siyuan, Shi Yaqian, Li Xin, Lu Min, Guo Wenli, Liu Yongcheng, Ou Yetao (Xin yixue, 2023)
Objective To investigate the pharmacological process of the effect of rapamycin upon the proliferation of triple-negative breast cancer MDA-MB-231 cells by regulating tumor necrosis factor receptor-associated protein 1 （TRAP1），and to unravel the anti-breast cancer mechanism of rapamycin. Methods MDA-MB-231 cells were randomly divided into the control group and different-dose rapamycin groups，and then the effect of rapamycin on cell proliferation was detected by MTT assay at 24 h and 48 h，respectively. Meantime，the half-maximal inhibitory concentration （IC50） of rapamycin was considered as the research condition. The effect of rapamycin on MDA-MB-231 cell cycle was detected by flow cytometry. The expression levels of mammalian target of rapamycin （mTOR），p-mTOR and TRAP1 proteins were detected by Western blot. The expression levels of mTOR and TRAP1 mRNA were measured by qPCR. ATP content was detected by ATP kit. The amount of lactic acid was determined by lactate assay kit. Results Rapamycin inhibited the proliferation of MDA-MB-231 cells in a dose- and time-dependent manner （P < 0.01）. The proliferation of MDA-MB-231 cells was decreased at 24 h and significantly decreased at 48 h after rapamycin treatment. IC50 was obtained at 10 μmol/L after 48 h. Rapamycin induced cell cycle arrest at G1 phase （P < 0.01）. Compared with the control group，the expression level of TRAP1 mRNA was significantly down-regulated （P < 0.05），and the expression levels of p-mTOR and TRAP1 proteins were significantly down-regulated （both P < 0.001），whereas the expression levels of mTOR mRNA and total mTOR protein were not significantly changed （both P > 0.05），the content of ATP was significantly increased （P < 0.001），and the content of lactic acid was significantly decreased （P < 0.001） in the 48-h rapamycin group. Conclusion Rapamycin can inhibit the proliferation of MDA-MB-231 cells by regulating the metabolic process，which is related to the decrease of TRAP1.